Variables associated with the relationship between obesity and mental health among university students in the Gulf Cooperation Council countries: a systematic review - Joma, Amjad; Abuzerr, Samer; Alsoudi, Sharif (Frontiers in Public Health, 2024)
Background: Various factors, including dietary habits, lifestyle choices, socio-economic status, cultural attitudes, academic stress, and access to mental health support services, influence the relationship between obesity and mental health among university students in Gulf Cooperation Council (GCC) countries. Understanding these complex interactions is crucial for developing effective interventions to promote both physical and mental well-being among students in the region. Therefore, this systematic review aims at understanding the variables associated with the relationship between obesity and mental health among university students in the (GCC) countries. Methods: This systematic review protocol was registered with the International Prospective Register of Systematic Reviews (PROSPERO)[CRD42024517806]. We conducted a systematic literature search using electronic databases including PubMed, PsycINFO, Scopus, CINAHL, Web of Science, and Google Scholar to identify relevant studies published up to 28-February-2024. A narrative synthesis approach was employed to summarize the findings of included studies. Data were synthesized according to predefined themes related to variables associated with the relationship between obesity and mental health among university students in GCC countries. Results: The prevalence of overweight and obesity among university students in GCC countries is alarmingly high, with a mean rate of 29.4%. Depression, anxiety, and body image dissatisfaction are significantly associated with obesity in this population. Poor sleep patterns are both a predictor and a consequence of obesity-related mental health issues. Socio-cultural factors play a crucial role in shaping students' perceptions of body image and mental health.These findings highlight the importance of comprehensive approaches to address the intertwined nature of obesity and mental health in this population, necessitating targeted interventions and further research efforts.